Arthropods associated with the crown of Mauritia flexuosa (Arecaceae) palm trees in three different environments from brazilian Cerrado - Gurgel Gonçalves, Rodrigo (2006)
Fil: Gurgel Gonçalves, Rodrigo. Laboratorio de Zoología. Universidad Católica de Brasília; Brasil.